The Shift of Gotong Royong Value of Karo Community in the Area around Mount Sinabung - Purba, Gufanta Hendryko; Sundawa, Dadang (Future Science, 2023)
This study is to find out the factors that Cause the shift in the value of gotong royong under the foot of Mount Sinabung. People who live in the foot of Sinabung mountain, used to be famous for the value of gotong royong that Inherent in every day of their daily life. Both in agriculture, as well as in traditional events, karo people have close values of gotong royong, in the form of joy and in the form of sorrow. However, at the time of the eruption, there was a huge impact on karo people, especially the shift in the value of gotong royong. So, the qualitative approach is chosen in this study with documentation methods, observation techniques and interviews. The findings of this study showed that as for the factors that led to the shift in the value of gotong royong among others, the eruption of Mount Sinabung, materialistic attitudes and individualistic lack of community participation in holding closely the value of gotong royong, plus the flow of modernization or globalization. It is expected that the government and the community cooperate to realize the values of gotong royong who are experiencing youth, socializing the planting of the value of gotong royong karo community, so that the younger generation will continue to preserve the value of gotong royong Karo community.